Konsentrasi Industri Dan Integrasi Industri Terhadap Ekonomi Industri Baru - Mahardhika Harilinawan; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to increase insight into the field of industrial economics, both conceptually and in its application in the development of industrial economics in Indonesia. This research focuses on systems, technology and transactions. The research method uses qualitative methods and library research. The data collection technique is to record important information in carrying out data analysis by means of data reduction, data display and drawing conclusions to obtain conclusions. The results of this research show that the existence of homogeneous industrial concentration and industrial integration will lead to economic growth and can create a new industrial economy.